Intraepithelial Melanoma in the Stomach After Treatment With Immune Checkpoint Blockade Therapy. (August 2017) - Shustef, Elina; Torres-Cabala, Carlos A.; Curry, Jonathan L.; Tetzlaff, Michael T.; Nagarajan, Priyadharsini; Ivan, Doina; Prieto, Victor G.; Aung, Phyu P.
Abstract : Abstract: Melanoma is the most common tumor to metastasize to the gastrointestinal tract, commonly affecting the small intestine, colon, and anorectum. Primary mucosal melanoma can arise in any gastrointestinal site, most frequently affecting anorectal mucosa. Melanoma involving the gastric mucosa, specifically, is exceedingly rare and carries a poor prognosis with a median survival of 5 months. The presence of atypical melanocytes exclusively within gastric epithelium has not been previously described. We report a case of a 52-year-old man with widespread BRAFV600E mutant metastatic melanoma who was referred to our institution for immune checkpoint antibody-blockade therapy. The patient had previously been treated with BRAF inhibitors, and despite initial response to therapy, developed resistance leading to disease progression and multiorgan involvement including the liver, spleen, and axial skeleton. Immune checkpoint antibody blockade with ipilimumab and pembrolizumab has been shown to induce significant tumor regression in patients with melanoma by upregulating T-cell activity and removing the natural check on the host immune response. After his first dose of combination therapy, the patient underwent an upper gastrointestinal tract endoscopy for severe nausea and was found to have 2 pigmented lesions within the gastric body, one of which was biopsied. The biopsy showed gastric body-fundic type mucosa with melanophages and scattered atypical intraepithelial melanocytes within the lamina propria, which were strongly positive for S100, HMB45, SOX10, and MITF. A Fontana-Masson silver stain was performed for confirmation. The finding of predominantly atypical intraepithelial melanocytes associated with melanin pigment was interpreted as metastatic melanoma to the stomach with some regression in response to immune checkpoint blockade therapy.